2022
DOI: 10.3390/ijms231911712
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols as Potent Epigenetics Agents for Cancer

Abstract: Human diseases such as cancer can be caused by aberrant epigenetic regulation. Polyphenols play a major role in mammalian epigenome regulation through mechanisms and proteins that remodel chromatin. In fruits, seeds, and vegetables, as well as food supplements, polyphenols are found. Compounds such as these ones are powerful anticancer agents and antioxidants. Gallic acid, kaempferol, curcumin, quercetin, and resveratrol, among others, have potent anti-tumor effects by helping reverse epigenetic changes associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 162 publications
0
26
0
Order By: Relevance
“…Polyphenols are very well-known antioxidants and thousands of scientific works have verified this activity for these ubiquitous natural compounds. A countless number of them, including many of those encountered in BP, have been conducted either at experimental or clinical levels, and have concerned many types of human diseases [ 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 ]. The development of these studies being beyond the scope of our current paper, we will not develop these results here.…”
Section: Resultsmentioning
confidence: 99%
“…Polyphenols are very well-known antioxidants and thousands of scientific works have verified this activity for these ubiquitous natural compounds. A countless number of them, including many of those encountered in BP, have been conducted either at experimental or clinical levels, and have concerned many types of human diseases [ 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 ]. The development of these studies being beyond the scope of our current paper, we will not develop these results here.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that RV can act epigenetically to modulate autophagy in cancer [ 22 - 24 ], and it is known that the secretions in the tumor microenvironment can epigenetically modulate autophagy to drive tumor dormancy [ 25 ]. In a separate study, we demonstrated that RV could keep ovarian cancer cells grown as 3D spheroids (a proxy of peritoneal metastatic colonies) in a dormant state even in the presence of IL-6, and this effect was due to the down-regulation of miR-1305 and concomitant re-expression of its target ARH-I (DIRAS3), which then rescued BECLIN-1-dependent autophagy [ 26 ].…”
Section: Main Subjectsmentioning
confidence: 99%
“…Among the mechanisms of anticancer activity of polyphenols are antioxidant/prooxidant activity, inhibition of specific protein kinases and other enzymes and the resulting changes in cellular signalling, inhibition of angiogenesis, estrogenic/antiestrogenic activity, antiproliferation, induction of detoxification enzymes, regulation of the host immune system, and anti-inflammatory activity [ 79 , 108 , 109 , 110 ]. Some polyphenols (e.g., quercetin, kaempferol, curcumin, resveratrol, and EGCG) downregulate the expression of histone deacetylases; this means that these compounds exert anticancer action by restoring epigenetic alterations in cancer cells as well as by DNA methylation and histone modifications which may prevent normal cells from turning into tumours [ 111 ]. It should be underlined that sirtuins (from SIRT1 to SIRT7) are enzymes belonging to class III HDAC (NAD+ −dependent histone deacetylases).…”
Section: Polyphenols In Disease Prevention and Treatmentmentioning
confidence: 99%